The Concept of an Unmanned Aircraft with Stealth Technology to Support the Air Defense System for the Indonesian Archipelago's Capital - Suherman Mukti; Erzi Agson Gani; Maykel Manawan; Ansori Ansori; Opa Mustopa (The Innovation of Social Studies Journal, 2023)
FPhenomenona The relocation of the new National Capital (IKN) in Indonesia creates a new geostrategic perspective. Where in the process must be prepared carefully, especially in the aspects of the defense and security system. This study aims to provide a planning analysis concept for Unmanned Aircraft (PTTA) with stealth technology in supporting air defense systems in Indonesia's new IKN area. The research method used is through a qualitative approach by conducting literature studies. The results of the study revealed that the air defense system for Indonesia's new IKN is in accordance with the concept of a smart defense system, the need for a platform/air vehicle that can be used in carrying out intelligence, surveillance, reconnaissance is even capable of carrying out attacks in maintaining security in the Indonesian IKN area by minimizing enemy detection. And one suitable platform is to use PTTA with stealth technology which can provide advantages in terms of flexibility, range, minimized operational risk, and the ability to carry out operations undetected by enemy defense radar sensors.